A tight polyethersulfone ultrafiltration membrane fabricated via polyion complex assisted phase inversion for dye desalination - Zhao, Yali (2023)
In this work, a tight polyethersulfone (PES) -based ultrafiltration (UF) membrane was fabricated to separate dye and salt of textile wastewater via a novel polyion complex assisted phase inversion method in one step. Thereinto, sulfonated polysulfone (SPSF) and poly-(diallyl dimethylammonium chloride) (PDADMAC) were added into the PES dope and coagulation bath, respectively. During the phase inversion process of the precast PES/SPSF film, polycation PDADMAC could assemble with anionic SPSF and facilitate SPSF enrichment on membrane surface, forming a dense barrier layer via the electrostatic interaction between quaternary ammonium and sulfonate groups. Morphology, chemical composition, surface charges and pore size analysis characterized via SEM, FTIR, XPS, Zeta potential and Dextran filtration experiment, respectively, testified that a nonporous skin layer comprising of polyion complex and enriched SPSF was successfully constructed on the top of the PES matrix with an effective pore radius of 1.44 nm, which is smaller than that of the reference membrane prepared without using polyion complex assisted phase inversion (2.74 nm). This resultant membrane exhibited a high pure water permeance of 94 LMH/bar. When it was utilized to separate a dye/salt mixture of 100 ppm Congo red (CR) and 2 g/L Na2SO4 at 1 bar, the rejection of CR could reach 99.7%, alongside a very low Na2SO4 rejection of 8.4%, while the water permeance of dye solution maintained 61 LMH/bar. In addition, the membrane also possessed excellent stability in the pH range of 1–13 due to the strong electrostatic interaction between SPSF and PDADMAC and long-term operation stability, demonstrating its application potential in textile wastewater treatment.